The Choice of the Foreign Touristic Destination: An Analysis of the Motivational Factors among the Algerian Tourists - Hadia Brahimi; Boubakeur Benlaib; Khaled Rouaski (Financial Markets, Institutions and Risks)
The objective of this study is to identify the motivational factors related to the choice of foreign touristic destinations among Algerian tourists. A questionnaire was distributed online and the study sample reached 318 Algerian tourists who visited at least one tourist destination outside of the country in 2018 or 2019. The data processing was done using the statistical software SPSS 28. The results showed on the one hand that the main internal motives for choosing a foreign destination are the desire to visit new places and see new natural landscapes, discover new cultures and lifestyles, and live a new travel experience. On the other hand, the main external motivations are the availability of the best quality-price ratio, the safety, and cleanliness of the destination, and the exceptional natural landscapes and historical sites.